Presentation as a way of translation skills developing - Perizat B. Sejtkazy; Amalia L. Kuregyan; Ekaterina A. Pertsevaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Currently, teaching almost every subject is accompanied by the creation of slide presentations, which are considered to be one of the most convenient and intuitive ways to process information. Moreover, this type of activity is also a way of the vocabulary drilling and a form of control of the topic studied in class, thus replacing monological speech on the material involved.The article presents the algorithm of working with the presentation as a way of translation skills formation of students studying at the Institute of Facultative Education of Samara State Technical University. This algorithm was derived from the analysis of presentations done by the students. The paper also provides recommendations for the effective presentations preparation in a foreign language. Such classes proved to be very effective: students do not have any difficulties with the presentation format, as it is discussed and worked out in advance; there is an idea of the most common mistakes in the presenting the information that should be avoided in their own speech, in addition, the audience is provided with a template that contains all the basic elements of the successful presentation. As a result, the students’ presentations are done at an extremely high level, which is one of the aspects of good preparation for the presentation in the final year of their studying.